The many lives of degrado: the affective, aesthetic and semiotic materiality of urban decay - Pavoni, A.; D'Alba, R. (Ethnography and Qualitative Research International Conference ERQ 2023 - 9th edition, 7-10 June, 2023)
two-session panel organised at the conference